Reflections on allyship in the context of a co-produced evaluation of a youth-integrated therapies mental health intervention. Issue 4 (2nd October 2021) - Gordon, Sarah; Dowell, Tony; Fedchuk, Dasha; Gardiner, Tracey; Garrett, Sue; Hilder, Jo; Mathieson, Fiona; Stubbe, Maria; Tester, Rachel
ABSTRACT: This paper reports on the reflections from members of the evaluation team – both allies and service user academics – about a co-produced approach to evaluation of the pilot of a youth-integrated therapies mental health intervention (co-evaluation). The co-evaluation is being facilitated particularly well through numerous service user academics being involved in the evaluation, and the commitment to co-production and active attendance to the responsibilities of allies by allies. However, multiple challenges still exist with significant implications for allyship. These include the need for us to 'deepen our thinking and approaches to best accomplish authentic and effective engagement' (Daya et al., 2020, 300) in support of co-production specific to the context of individual projects, the fluidity of the allyship position and the need for allies to consistently reinforce their commitment in word and in deed to it. We have also identified the need to acknowledge and respect the distinction between people in roles who happen to have experience and people in roles because they have experience .